Determination of stage specific markers for liver fibrosis in hepatitis B: A comparative tissue proteomic study - Katrinli, Şeyma; Özdil, Kamil; Şahin, Aslı; Öztürk, Oğuzhan; Kır, Gözde; Baykal, Ahmet Tarık; Saraç, Ömer Sinan; Sökmen, Mehmet; Dinler Doğanay, Gizem; Doğanay, Hamdi Levent (Elsevier Science B.V., 2016)
Background and Aims: Chronic Hepatitis B infection is one of themajor causes of liver cirrhosis and around 600,000 people dieannually worldwide. The virus itself is non-cytopathic and the liverdamage is due to host immune reaction. Thus liver damage pathwaysmight differ in chronic HBV and comprehensive tissue proteomicanalysis is missing in literature. To estimate which patient withchronic hepatitis B will develop rapidly fibrosis or cirrhosis is yet athorny issue and requires a vast recognition of cellular pathwaysinvolved in fibrosis. The aim of this study is to enlighten pathwaysassociated with liver fibrosis in HBV infection for leading up to newtherapeutic targets and diagnostic biomarkers.
EASL International Liver Congress -- APR 13-17, 2016 -- Barcelona, SPAIN
WOS: 000398711700732
Keywords: Hepatitis B; Liver Fibrosis; Specific Markers